Foot Exercise Therapy to Alleviate Peripheral Neuropathy Severity in Elderly Patients with Diabetes Mellitus - Wahyu Nur Pratiwi; Giovanni Iga Firmanda; Rita Dewi Sunarno; Paramita Ratna Gayatri; Arshy Prodyanatasari (Adi Husada Nursing Journal, 2025)
Foot neuropathy is a common condition experienced by older adults with diabetes mellitus. This complication can be managed through physical activity, including foot exercises. This study aimed to evaluate the effect of foot exercises on the severity of foot neuropathy in older adults with diabetes mellitus at the Tarokan Community Health Center. This quasi-experimental study employed a non-equivalent control group design and involved 30 older adults with diabetes mellitus who exhibited neuropathic symptoms. Participants were divided into two groups: 15 individuals in the intervention group and 15 in the control group, selected through purposive sampling. The intervention group performed foot exercises three times per week for three weeks, with each session lasting 15–20 minutes. A 10 g monofilament and an observation sheet were used as instruments, and data were analyzed using the Wilcoxon and Mann–Whitney tests. The Wilcoxon test revealed a significant reduction in the degree of foot neuropathy in the intervention group (p = 0.001), whereas the control group showed no significant change (p = 0.527). The Mann–Whitney test indicated a significant difference between the two groups (p = 0.000). These findings demonstrate that foot exercises effectively reduce the severity of foot neuropathy in older adults with diabetes mellitus. Regular implementation of foot exercises is recommended as a non-pharmacological approach to decreasing the degree of foot neuropathy among older adults with diabetes mellitus.